Two new species of Umbonichiton (Hemiptera: Sternorrhyncha: Cocccoidea: Coccidae) from New Zealand - Henderson, Rosa C.; Hodgson, Chris J. (Zootaxa, 2005)
The Coccidae of New Zealand were revised recently and the genus Umbonichiton introduced to include five species, four of which were described as new. This paper describes another two new species, Umbonichiton bispinatus Henderson & Hodgson and Umbonichiton rimu Henderson & Hodgson, both of which are known only from the podocarp Dacrydium cupressinum. The two species appear to be closely related. The genus Umbonichiton is re-diagnosed and a key is presented for the separation of the adult females.